Sözlü Tanıkların Dilinde Çanakkale'de Öğretmen Yetiştiren Kurumların Tarihi (1915-1992) - Selçuk UYGUN (Çanakkale Araştırmaları Türk Yıllığı, 2010)
The aim of this research is to define the effect of teacher training institutions through oral history method. The first continually teacher training institution in Çanakkale was opened in 1956. In later years, this institution had continued educational period under different names, and it was been basis of Çanakkale Onsekiz Mart University founded in 1992. This research is important. Because it presents a review of the history of teacher training institutions in (in particular) and its results will be clarified to general teacher training (in general). The oral history researches that were made with teachers who graduated from the teacher education institutions except Faculty of Education in Çanakkale and the effects of institutions on historical development process have been reviewed in comparative way. Data was collected from narrations of witness and document analysis. These data was analyzed and evaluated in a descriptive way. According to findings, it has been seen that witnessing that based oral history method as important as printed sources to clarify institutions’ social and cultural development.